Mechanisms for deformation induced hexagonal close-packed structure to face-centered cubic structure transformation in zirconium. (15th April 2017) - Zhao, Henglv; Hu, Xinyi; Song, Min; Ni, Song
Abstract: Two distinctive orientation relations between hexagonal close-packed (HCP) phase and face-centered cubic (FCC) phase were observed simultaneously in cold-rolled pure Zr, which were denoted as B-type and P-type orientation relations according to whether the phase interface is parallel to the basal plane or prism plane of the HCP matrix. The mechanisms for the phase transformation generating the two different HCP-FCC orientation relations were thoroughly analyzed. B-type orientation relation was achieved when HCP to FCC phase transformation occurred via collective gliding of Shockley partial dislocations on basal planes, while P-type orientation relation was attained through pure-shuffle and shear-shuffle mechanisms. Graphical abstract: